Enhanced Cellulose Content in Microwave-Assisted Sulfuric Acid Pretreatment of Java Grass - Cahyono, Agung; Khotimah, Mujaroh; Ashabi, Arman (Universitas Brawijaya, 2024)
This study investigated the enhancement of cellulose content in Java grass (Cyperus rotundus) through microwave-assisted sulfuric acid pretreatment. The research involved soaking Java grass in varying concentrations of H2SO4 (1.5%, 3%, and 4.5%) and subjecting it to microwave irradiation at 2450 MHz for different durations (25, 35, and 45 minutes). The results showed that the highest cellulose content of 43.61% was achieved with a 1.5% H2SO4 solution for 45 minutes, representing a 90.3% increase from the pre-treatment level of 22.91%. The microwave-assisted pretreatment effectively disrupted the lignocellulosic structure, reduced cellulose crystallinity, and increased biomass surface area, thereby enhancing enzymatic hydrolysis. However, an anomaly was observed in the lignin content, which increased from 14.3% to 36.65% post-treatment, likely due to errors in lignin determination and the formation of pseudo-lignin.